The Scottish Referendum 2014: the Political Process Before and After the “No” Vote’ - Antunes, Sandrina Ferreira (2016)
On 18 September 2014, Scottish voters narrowly rejected political independence, losing 44.7% to 55.3%. Yet during more than 16 weeks, two opposing campaigns – Yes Scotland versus Better Together – strove to convince Scotland that political independence versus keeping the Union was the best choice for Scotland’s future. Filled with many unexpected moments, the campaign was intense, vibrant and almost breath-taking. The purpose of this article is to deliver a coherent and consistent account of the Scottish campaigns in order to make sense of the ‘No’ vote. In this article, we will proceed in four sections: first, we will put the referendum in context; second, we will highlight major aspects of the campaigns; third, we will bring the political process up-to-date and clarify the terms of the agreement reached under the Smith Process. Finally, in the last part, we will summarise the lessons to learn from the political outcome of the referendum.